Current technologies for plastic waste treatment: A review. (1st February 2021) - Zhang, Fan; Zhao, Yuting; Wang, Dandan; Yan, Mengqin; Zhang, Jing; Zhang, Pengyan; Ding, Tonggui; Chen, Lei; Chen, Chao
Abstract: Conventional nonbiodegradable plastic waste (NPW) treatment technologies include landfill and incineration, which face bottlenecks and cannot solve NPW problems effectively. Therefore, many advanced NPW treatment technologies have been reported. This review summarizes currently reported advanced NPW treatment technologies, analyzes their mechanisms and development status, and proposes an outlook for their industrial application based on the gap between the current development status and industry requirements. The technologies are introduced based on basic classification into two strategies: recycling and degradation. Recycling technologies are further categorized into three subtypes: physical recycling, energy recovery, and resource recovery. Degradation technologies are further categorized into two subtypes: biodegradation and oxo-biodegradation. Oxo-biodegradation is divided into abiotic degradation and biotic degradation. Abiotic degradation includes photodegradation, thermodegradation, mechanochemical degradation and other degradation techniques. The mechanisms for pyrolysis and photodegradation are systematically summarized. The purpose of this review is to provide readers with a comprehensive introduction to various advanced NPW treatment technologies, which can enable readers to understand the development status and outlook of the technology. Highlights: Plastic waste disposal technologies are reviewed based on recycling and degradation. The mechanisms for pyrolysis and photo-degradation are systematically summarized. Actual gasoline-range yield is proposed to assess the actual pyrolysis performance. Ideal photodegradable plastic model with indicating color change node is proposed.